Analisis Gaya Bahasa Sarkasme dan Satire dalam Novel “Orang-Orang Oetimu” Karya Felix K. Nesi - Djeni Novianti Debora Lona; Marselus Robot; Narantoputrayadi Makan Malay (YASIN, 2026)
Sarcasm and satire in literary works serve as means of conveying social criticism with contextual and profound meanings. This study aims to describe the forms of sarcasm and satire and to reveal the meanings contained in the novel Orang-Orang Oetimu by Felix K. Nesi. The study employed a qualitative descriptive method with a stylistic approach. The research data consisted of words, phrases, sentences, and dialogues containing sarcasm and satire. The data were collected through critical reading, coding, and note-taking and were then analyzed by identifying, classifying, and interpreting their meanings based on the context of the story. The results revealed 27 instances of sarcasm and 11 instances of satire. Sarcasm was used to express anger, insult, disappointment, and criticism directly through harsh and sharp words. Meanwhile, satire was used to convey indirect social criticism of social, political, moral, and societal behavioral issues. The findings showed that sarcasm was used more dominantly than satire. In addition, the use of local terms from Timorese communities strengthened the linguistic characteristics and the expression of criticism in the novel. This study confirms that figurative language in Orang-Orang Oetimu functions not only as an aesthetic element but also as a medium of social criticism and meaning construction. These findings contribute to the development of stylistic studies and literary analysis, particularly in understanding the functions of sarcasm and satire in representing social realities.